A participação do futuro morador em projetos habitacionais de baixa renda: estudos de caso - Leandro de Aguiar e Souza (2007)
The present work investigates the participation of users in projects of lowincome housing through the study of three experiences linked to the accord, firmed in Belo Horizonte city in 2004, between the programs Crédito Solidário, Moradias por Auto Gestão e Orçamento Participativo da Habitação. The objective of the research was to discuss, from the study of the projects Residencial Serra Verde, Santa Rosa 02 e Castelo 01, how this participation occurred, analyzing the stages understood between the land definition and the moment that the architectonic solutions had been given by locked up. The research has two main parts: the first one consists in the review of the literature, witch is the quarrel about the historical bases of the Brazilian participativepublic policies, been boarded, at a first moment, the process marked by the absence of participation. At a second moment, the changes occurred after the Constitution of 88 are discussed, witch made possible the creation of legal instruments for the establishment of the studied participative process. The second part is built up by the analysis and discussion of the primary data, in which looked up to identify the potentialities and limitations, not only from the researched process as well the housing policy in question. This studies results, presented in the conclusions and final considerations, show that longed for participation still very limitated under many aspects, distinguishing the high number of families, participants of the projects, disapproved later in the process of loan programme, and the economic and operational limitations that make impossible an effective and ample cooperation. However, theses limitations could not be excuse to invalidate the potential of the participation in produce houses of low budget more adjusted to the needs of its future residents.